Modulation of Host miRNAs Transcriptome in Lung and Spleen of Peste des Petits Ruminants Virus Infected Sheep and Goats - Pandey, Aruna; Sahu, Amit R.; Wani, Sajad A.; Saxena, Shikha; Kanchan, Sonam; Sah, Vaishali; Rajak, Kaushal K.; Khanduri, Alok; Sahoo, Aditya P.; Tiwari, Ashok K.; Mishra, Bina; Muthuchelvan, D.; et al. (Frontiers in Microbiology, 2017)
Peste des petits ruminants (PPR) is one of the highly contagious viral disease, characterized by fever, sore mouth, conjunctivitis, gastroenteritis and pneumonia, primarily affecting sheep and goats. Reports suggested variable host response in goats and sheep and this host response vis – a – vis the expression of miRNAs has not been investigated. Here, miRNAs were sequenced and proteomics data were generated to identify the role of differentially expressed miRNA in PPRV infected lung and spleen tissues of sheep and goats. In lungs, 67 and 37 differentially expressed miRNAs (DEmiRNAs) have been identified in goats and sheep, respectively. Similarly, in spleen, 50 and 56 DEmiRNAs were identified in goats and sheep, respectively. A total of 20 and 11 miRNAs were found to be common differentially expressed in both the species in PPRV infected spleen and lung, respectively. Six DEmiRNAs - miR-21-3p, miR-1246, miR-27a-5p, miR-760-3p, miR-320a and miR-363 were selected based on their role in viral infections, apoptosis and fold change. The target prediction analysis of these six selected DEmiRNAs from the proteome data generated, revealed involvement of more number of genes in lung and spleen of goats than in sheep. On gene ontology analysis of host target genes these DEmiRNAs were found to regulate several immune response signaling pathways. It was observed that the pathways viz. T cell receptor signaling, Rap1 signaling, Toll-like receptor signaling and B cell receptor signaling governed by DEmiRNAs were more perturbed in goats than in sheep. The data suggests that PPRV-induced miR-21-3p, miR-320a and miR-363 might act cooperatively to enhance viral pathogenesis in the lung and spleen of sheep by downregulating several immune response genes. The study gives an important insight into the molecular pathogenesis of PPR by identifying that the PPRV - Izatnagar/94 isolate elicits a strong host response in goats than in sheep.